Democratisation and Educational Inclusion during Lockdown Times: Perceptions of Portuguese Teachers - Leonor L. Torres; Mariana Gaio Alves (MDPI AG, 2024)
The COVID-19 pandemic had a significant impact on school education, as confirmed by numerous studies produced at the international level. One of the most profound effects was the potential change to the political mandates of schools and resulting alterations in professional teaching practices, given the proliferation of remote (online and blended) teaching. This article aims to explore the extent to which the pandemic crisis has reconfigured schools' educational priorities, with an emphasis on democratisation and inclusion at the expense of learning outcomes and meritocratic approaches. Based on an extensive study as part of a wider international project, the results of a questionnaire survey of Portuguese teachers (n = 3983) during the initial lockdown period in 2020 are analysed. The empirical evidence suggests that the pandemic resulted in a strengthening of the democratising pole, underpinned by the principles of equal opportunities, inclusion, and social justice, even though the practices and priorities of teachers as a whole are not homogeneous. This heterogeneity reflects pre-existing professional and school cultures, which vary depending on level of education, gender, school type, and career length, among other important factors.